Ewolucja systemu gospodarczego Rosji: uwarunkowania, etapy i perspektywy zmian - Fiedorczuk, Monika (Annales. Etyka w Życiu Gospodarczym, 2019)
The political and economic reforms in Russia since the beginning of the 1990s have made it possible to build a new economic system. Over more than 25 years, this system has evolved under the influence of, among others, economic and financial crises, which resulted in changes in the role of the state, ownership structure and the specificity of the corporate sector. The main goal of the paper is to identify the key elements and features of the economic system in Russia in the specified stages of its evolution and to indicate the perspectives of changes. To achieve this goal, an in-depth analysis was made of the literature and statistical data. The author puts forward the thesis that there are still some premises of the evolution of the economic system in Russia which resulted from the need for structural changes and the exhaustion of the current model of economic growth. However, in the immediate future, the economic system in Russia will not evolve significantly because of the economic stability and the lack of political will to make significant reforms.